Eksistensi Sanksi Kerja Sosial Dalam Kuhp Nasional Sebagai Upaya Penanggulangan Overcrowding Pemasyarakatan - Anisah Friti Anjelia; Elsa Ramadhana; Sutra Oktaviani; Ruben Malau; Ria Anggraeni Utami (GLOBAL SCIENTS PUBLISHER, 2026)
This study analyzes the provision of community service sanctions under the Indonesian Criminal Code (KUHP Nasional) as a viable alternative to conventional sentencing aimed at mitigating overcrowding in correctional facilities. Imprisonment remains the cornerstone of criminal justice enforcement in Indonesia, leading to escalating inmate populations that far exceed available prison capacities. Consequently, this has engendered multiple challenges, such as diminished rehabilitation efficacy, inadequate amenities, and elevated tensions among inmates (Directorate General of Corrections, 2023). Adopting a normative methodology, the research scrutinizes the statutory provisions for community service sanctions and their prospective integration into criminal adjudication processes. Results affirm that these sanctions represent a more humane and proportionate punitive measure, extending beyond retribution to encompass offender restoration and societal reintegration (Articles 70-72, KUHP Nasional). Moreover, their adoption holds substantial promise for alleviating pressures on penitentiary systems. Nonetheless, deployment encounters hurdles including law enforcement preparedness, insufficient technical protocols, and constrained field-level resources. Hence, resolute collaboration among key stakeholders is imperative to facilitate the efficacious and enduring enforcement of community service sanctions.